Wykorzystanie podejścia zagregowanego w taksonomii - Rozmus, Dorota (Cluster Ensemble, 2008)
Ensemble methods are used in classification and regression to achieve better prediction accuracy. Recent research reveals that ensemble methods can be used also in taxonomy in order to gain better and more robust objects' classification [Fred, Jain 2005; Kuncheva et al. 2006]. Moreover aggregated approach decreases the risk of gaining a wrong classification because of choosing an unsuitable algorithm. The main aim of the article is to show the possibility of applying one of the most popular ensemble methods, which is bagging [Breiman 1996] in taxonomy. We also show the results of research that main aim was to compare the results of classification with using both classical and ensemble methods with the existing class structure.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 330-336